PERKEMBANGAN POLITIK HUKUM PERTAMBANGAN MINERAL DAN BATUBARA DAN IMPLIKASINYA BAGI MASYARAKAT HUKUM ADAT - Erika, Erika (Jurnal Yuridis, 2018)
The problem of land conflicts in the territory of Ulayat Land of Customary Law Community conducted by the company as an investment actor conducting business activities in the field of mineral and coal mining and its settlement efforts can not be explained through the only normative juridical approach, but the holistic and integrative approach. Approaches known in social science, sociology, and legal anthropology can be used to explain the issue of dispute resolution based on local potential. The choice of conflict resolution of conflicts arising from unequal distribution and management of resources and unequal power and authority, to address these types of conflicts should be put forward with justice and benefit as the main objective, not the legal certainty aspect.